Serum Concentration of Erlotinib and its Correlation with Outcome and Toxicity in Patients with Advanced-stage NSCLC - Fiala, Ondrej; Hosek, Petr; Pesek, Milos; Finek, Jindrich; Racek, Jaroslav; Stehlik, Pavel; Sorejs, Ondrej; Minarik, Marek; Benesova, Lucie; Celer, Adam; Nemcova, Ivana; Kucera, Radek; et al. (Anticancer research, 2017)
BACKGROUND: Erlotinib is a tyrosine kinase inhibitor targeting epidermal growth factor receptor (EGFR); it is used in the treatment of advanced non-small cell lung cancer (NSCLC). We focused on the role of serum concentration of erlotinib and its association with outcome and toxicity in patients with advanced NSCLC harbouring the wild-type EGFR gene or squamous histology. PATIENTS AND METHODS: Clinical data of 122 patients were analyzed. Serum samples were collected within four weeks after the initiation of treatment. RESULTS: There was no significant association of erlotinib concentration with PFS nor OS (p=0.352 and p=0.6393). Significant associations of erlotinib concentration with grade of skin rash and diarrhoea (p<0.0001 and p<0.0001) were found. Skin rash and diarrhoea were significantly associated with PFS (p=0.0338 and p=0.0001) and OS (p=0.0064 and p=0.0353). CONCLUSION: Erlotinib concentration was not associated with outcome. Erlotinib concentration was associated with occurrence and severity of skin rash and diarrhoea; the outcome was associated with erlotinib toxicity.
Keywords: erlotinib; lung cancer; přežití bez známek nemoci; Disease-Free Survival; retrospektivní studie; Humans; staging nádorů; nemalobuněčný karcinom plic; Erlotinib; exantém; Neoplasm Staging; Antineoplastic Agents; Lung Neoplasms; serum concentration; protinádorové látky; erbB receptory; průjem; mužské pohlaví; nádory plic; skin rash; toxicity; výsledek terapie; survival; ErbB Receptors; Treatment Outcome; ženské pohlaví; Diarrhea; NSCLC; Carcinoma, Non-Small-Cell Lung; lidé; Erlotinib Hydrochloride; Exanthema; diarrhoea; analýza přežití; Male; Retrospective Studies; Survival Analysis; Female